Eliminate bacterial resistance to antibiotics through synergistic effect with plant essential oils - Alaa Hayder; Muhsin Essa (College of Education for Pure Sciences, 2021)
This study was conducted with the aim of evaluating the ability of the synergistic effect of nine plant essential oils with antibiotics in removing the antibiotic resistance characteristic of the multiple drug resistance pathogenic bacteria. The disc diffusion method was used for this purpose and the oils were synergized with antibiotics showed resistance by the studied bacteria. The results showed a synergistic effect (ranged between 3 - 40 mm) for different oils with antibiotics according to the type of bacteria, that the most numerous cases of synergism (27 cases) were with P.mirabilis and the highest synergistic inhibition occurred with the same bacteria (40 ml). Pomegranate seed oils, thyme, rosemary and cinnamon were able to synergize with six antibiotics, while eucalyptus, Peppermint, ginger and orange synergized with five, Lavender oil synergized with four antibiotics. We conclude from the results of this study the possibility of combining plant essential oils with antibiotics to remove resistance, which opens the door to finding new ways to treat many diseases caused by multiple drug resistance pathogens.